Comparison of air, road, time and cost distances in Hungary - Tamas Dusek (European Regional Science Association (ERSA), 2010)
The aim of this study is to discuss the differences between geographical, road, time and cost distances by the help of the Hungarian railway network and road network data. The first section deals with the general characteristics of distances and spaces and the validity of metrical axioms in time and cost space. Time and cost space are more complex than geographical space, because there is just one and only air kilometers and the kilometer distance between points of network can be determined more or less exactly. Time distances and cost distances fall into an interval and at best only about shortest or typical distances, shortest or typical lengths of time and least or typical costs can be spoken. The second and third sections compare local and global the geographical space and various road, time and cost spaces, first by the help of detour indices and then with multidimensional scaling.
Keywords: 330